“An Intense Level of Self-regulation”: Technological Opportunities and Limitations of Online Intergroup Dialogue - Grant Jackson; Sarah Schiffecker; Oleksandra Poquet (Journal of the Scholarship of Teaching and Learning)
Nationwide, postsecondary institutions are seeing the need and searching for ways to prepare their students for life in an increasingly complex and often polarized society. Since its development in the 1980s, intergroup dialogue (IGD) has become a nationally prominent social justice pedagogy that brings together small, diverse groups of college students to dialogue on topics related to diversity, equity, belonging, and social justice. Though IGD has traditionally been an in-person experience, the COVID-19 pandemic required colleges and universities to facilitate IGD online. Given this sudden and unprecedented transition to online delivery, as well the resulting possibility that IGD (along with other similar efforts) could become increasingly online going forward, it becomes important to discern the technological opportunities and limitations that come with such online delivery. In this study, we interviewed 16 college students who had participated in IGD via Zoom regarding their online IGD experience, illuminating a variety of opportunities and limitations related to students’ use of cameras, microphones, and the chat feature; the physical spaces in which students experienced their online IGD; the online display of students’ IGD peers; students’ engagement in multi-tasking during IGD sessions; students’ experiences of small group activities in “breakout rooms”; and how the online delivery of IGD promoted and constrained students’ sense of equity and equality throughout their IGD experience. Implications of these findings for IGD practice and future research are discussed.